Wound healing: Natural history and risk factors for delay in Australian patients treated with antibiotics for Mycobacterium ulcerans disease. - Daniel P O'Brien; N Deborah Friedman; Anthony McDonald; Peter Callan; Andrew Hughes; Aaron Walton; Eugene Athan (Public Library of Science (PLoS), 2018)
Healing times following treatment with antibiotics, and factors that influence healing, have not been reported in Australian patients with Mycobacterium ulcerans.Healing times were determined for all M. ulcerans cases treated by a single physician with antibiotics at Barwon Health, Victoria, from 1/1/13-31/12/16. Lesions were categorised by induration size: category A ≤ 400mm2, Category B 401-1600mm2 and Category C ≥1601mm2. A logistic regression analysis was performed to determine risk factors for prolonged wound healing (>150 days from antibiotic commencement). 163 patients were included; 92 (56.4%) were male and median age was 58 years (IQR 39-73 years). Baseline lesion size [available in 145 (89.0%) patients] was categorised as A in 46 (31.7%), B in 67 (46.2%) and C in 32 (22.1%) patients. Fifty (30.7%) patients had surgery. In those treated with antibiotics alone, 83.0% experienced a reduction in induration size after 2 weeks, then 70.9% experienced an increase in induration size from the lowest point, and 71.7% experienced an increase in ulceration size. A linear relationship existed between the time induration resolved and wound healing began. Median time to heal was 91 days (IQR 70-148 days) for category A lesions; significantly shorter than for category B lesions (128 days, IQR 91-181 days, p = 0.05) and category C lesions (169 days, IQR 159-214 days, p<0.001). Fifty-seven (35.0%) patients experienced a paradoxical reaction. Of those treated with antibiotics alone, lesions experiencing a paradoxical reaction had longer healing times [median time to heal 177 days (IQR 154-224 days) compared to 107 days (IQR 79-153 days), p<0.001]. On multivariable logistic regression, lesion size at baseline (p<0.001) and paradoxical reactions (p<0.001) were independently associated with prolonged healing times. For category A and B lesions, healing time was significantly shorter with antibiotics plus excision and direct closure compared with antibiotics alone [Category A lesions median 55 days (IQR 21-63 days) compared with 91 days (IQR 70-148 days), p<0.001; Category B lesions median 74 days (IQR 21-121 days) compared to 128 days (IQR 97-181 days), p<0.001].In Australian patients treated with antibiotics M. ulcerans lesions usually initially improve, then clinically deteriorate with increased induration and ulceration, before healing after the inflammation associated with lesions resolves. The time to complete healing of lesions is generally long, and is further prolonged in those with larger initial lesion size or who develop paradoxical reactions. For small lesions (<4cm2), excisional surgery may reduce healing times.